Disruption of the GluA2/GAPDH complex using TAT-GluA2NT1-3-2 peptide protects against AMPAR-mediated excitotoxicity after epilepsy. Issue 5 (21st March 2018) - Zhang, Jinghui; Qiao, Nana; Ding, Xiufang; Wang, Jiwen
Abstract : Excitotoxicity and neuronal death following epilepsy involve α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptors (AMPARs). It forms a protein complex with glyceraldehyde-3-phosphate dehydrogenase (GAPDH) and co-internalizes upon activation of AMPA receptors after epilepsy. Disruption of the GluA2/GAPDH complex with an interfering peptide, TAT-GluA2NT1-3-2, protects cells against AMPAR-mediated excitotoxicity, which have been identified in in-vitro and in-vivo models of brain ischemia. We postulated that disruption of the GluA2/GAPDH interaction with the TAT-GluA2NT1-3-2 peptide would also protect against AMPAR-induced neuronal injury in an in-vivo model of status epilepticus (SE). In the present study, we divided pilocarpine-induced SE Wistar rats into three main groups: the TAT-GluA2NT1-3-2 peptide group, the TAT-GluA2NT-scram peptide group, and the normal saline group, and injected different doses of peptides stereotaxically into the hippocampus of SE rats to investigate whether the GluA2/GAPDH interaction could be disrupted by our TAT-GluA2NT1-3-2 peptide and determine its most appropriate dose. Then, the dose was administered stereotaxically at different time points after SE to determine the best administration time of neuronal protection. We found that the TAT-GluA2NT1-3-2 peptide can disrupt the GluA2/GAPDH interaction and protects against epilepsy-induced neuronal damage. The GluA2/GAPDH interaction may be a novel therapeutic target for epilepsy.